Monitoring a Norwegian freshwater crayfish tragedy: eDNA snapshots of invasion, infection and extinction. Issue 7 (16th May 2019) - Strand, David A.; Johnsen, Stein Ivar; Rusch, Johannes C.; Agersnap, Sune; Larsen, William Brenner; Knudsen, Steen Wilhelm; Møller, Peter Rask; Vrålstad, Trude
Abstract: The European noble crayfish Astacus astacus is threatened by crayfish plague caused by the oomycete Aphanomyces astaci, which is spread by the invasive North American crayfish (e.g. signal crayfish Pacifastacus leniusculus ). Surveillance of crayfish plague status in Norway has traditionally relied on the monitoring survival of cage‐held noble crayfish, a method of ethical concern. Additionally, trapping is used in crayfish population surveillance. Here, we test whether environmental DNA (eDNA) monitoring could provide a suitable alternative to the cage method, and a supplement to trapping. We took advantage of an emerging crayfish plague outbreak in a Norwegian watercourse following illegal introduction of disease‐carrying signal crayfish, and initiated simultaneous eDNA monitoring and cage‐based surveillance, supplemented with trapping. A total of 304 water samples were filtered from several sampling stations over a 4‐year period. eDNA data (species‐specific quantitative real‐time PCR [qPCR]) for the presence of A. astaci, noble and signal crayfish within the water samples were compared to cage mortality and trapping. This is the first study comparing eDNA monitoring and cage surveillance during a natural crayfish plague outbreak. We show that eDNA monitoring corresponds well with the biological status measured in terms of crayfish mortality and trapping results. eDNA analysis also reveals the presence of A. astaci in the water up to 2.5 weeks in advance of the cage method. Estimates of A. astaci and noble crayfish eDNA concentrations increased markedly during mortality and vanished quickly thereafter. eDNA provides a snapshot of the presence, absence or disappearance of crayfish regardless of season, and constitutes a valuable supplement to the trapping method that relies on season and legislation. Synthesis and applications . Simultaneous eDNA monitoring of Aphanomyces astaci (crayfish plague) and relevant native and invasive freshwater crayfish species is well‐suited for early warning of invasion or infection, risk assessments, habitat evaluation and surveillance regarding pathogen and invasive/native crayfish status. This non‐invasive, animal welfare friendly method excludes the need for cage‐held susceptible crayfish in disease monitoring. Furthermore, eDNA monitoring is less likely to spread A. astaci than traditional methods. This study resulted in the implementation of eDNA monitoring for Norwegian crayfish plague and crayfish surveillance programmes, and we believe other countries could improve management strategies for freshwater crayfish using a similar approach. Abstract : Simultaneous eDNA monitoring of Aphanomyces astaci (crayfish plague) and relevant native and invasive freshwater crayfish species is well‐suited for early warning of invasion or infection, risk assessments, habitat evaluation and surveillance regarding pathogen and invasive/native crayfish status. This non‐invasive, animal welfare friendly method excludes the need for cage‐held susceptible crayfish in disease monitoring. Furthermore, eDNA monitoring is less likely to spread A. astaci than traditional methods. This study resulted in the implementation of eDNA monitoring for Norwegian crayfish plague and crayfish surveillance programmes, and we believe other countries could improve management strategies for freshwater crayfish using a similar approach. Sammendrag: Europeisk edelkreps ( Astacus astacus ) trues av krepsepest som forårsakes av eggsporesoppen Aphanomyces astaci . Smitten spres av fremmed nordamerikansk ferskvannskreps (f.eks. signalkreps; Pacifastacus leniusculus ). Overvåking av krepsepest i Norge har tradisjonelt basert seg på burforsøk, en etisk problematisk metode hvor dødelighet hos edelkreps i bur overvåkes ved relevante lokaliteter. Overvåking av edelkrepsbestander blir gjort ved bruk av teiner. Vi har testet om overvåking basert på innsamling av miljø‐DNA (eDNA) kan være et egnet alternativ til burforsøk, og et supplement til teinefangst. Etter en ulovlig introduksjon av smittebærende signalkreps i en innsjø med edelkreps, utnyttet vi vissheten om et kommende krepsepestutbrudd til å initiere eDNA‐overvåking og burforsøk samtidig, supplert med teinefangst. Tilsammen ble 304 vannprøver filtrert fra ulike prøvetakingsstasjoner over en fire‐års periode. eDNA data (arts‐spesifikk qPCR) for tilstedeværelse av A. astaci, edelkreps og signalkreps i vannprøver ble sammenlignet med dødelighet i burforsøk og teinefangst. Dette er den første studien som sammenligner eDNA‐overvåkning og burforsøk under et naturlig krepsepestutbrudd. Vi viser at eDNA‐overvåking korresponderer godt med biologisk status målt i form av dødelighet hos burkreps og resultater fra teinefangst. eDNA‐analyser avslører også tilstedeværelsen av A. astaci smittestoff i vannet opptil 2, 5 uker før edelkreps dør i burforsøk. Mengdeestimater av eDNA fra A. astaci og edelkreps i vannet økte markant under dødelighet, og forsvant deretter raskt. Uansett årstid gir eDNA et øyeblikksbilde av tilstedeværelse, fravær eller bortfall av edelkreps, og utgjør derfor også et verdifullt supplement til teinefiske, som avhenger av sesong og nasjonal lovgivning. Syntese og bruksområder. Parallell eDNA‐overvåkning av Aphanomyces astaci (krepsepest agens) og relevante stedegne og fremmede arter av ferskvannskreps er velegnet for tidlig varsling av invasjon og smitte, risikovurderinger, evaluering av habitatstatus, og overvåking av status for smittestoff og fremmed/stedegen ferskvannskreps. Metoden er dyrevelferdsvennlig, og utelukker behovet for burforsøk med levende kreps i sykdomsovervåking. Videre gir eDNA‐overvåkning mindre sannsynlighet for å spre Aphanomyces astaci smitte enn tradisjonelle metoder. Denne studien har bidratt til å implementere eDNA‐overvåking i norsk overvåkning av krepsepest, edelkreps og signalkreps, og vi tror at andre land også kan forbedre sine forvaltningsstrategier for ferskvannskreps ved hjelp av en lignende tilnærming.